The Bamberg Trucking Game: A Paradigm for Assessing the Detection of Win–Win Solutions in a Potential Conflict Scenario - Nalis, Dario; Schütz, Astrid; Pastukhov, Alexander (Frontiers in Psychology, 2018)
When win-win solutions are identified, all parties benefit more from the solution than they would if they each pursued their own individual goals. Such solutions are beneficial at individual and collective levels and thus represent optimal solutions. Win-win solutions are desirable but often difficult to find. To contribute to the study of individual differences and situational factors that help or hinder the detection of win-win solutions, we created a paradigm that fills a gap in the repertoire of psychological instruments used to assess collaboration, cooperation, negotiation, and prosocial behavior. The new paradigm differs from previous ones in two respects: (a) In existing paradigms that focus on social motivation, the possible strategies are evident, whereas we focused here on the question of whether people could detect the solution, and thus, we disentangled ability from motivation, and (b) paradigms that focus on cooperation typically entail a risk associated with the partner’s defection, whereas cooperation in our paradigm is not associated with risk. We adjusted the Trucking Game—a method for assessing bargaining—to include a situation in which two parties can help each other achieve their respective goals and thus benefit over and above the pursuit of individual goals or compromises. We tested scenario-based and interaction-based versions with samples of 154 and 112 participants, respectively. Almost one third of the participants or dyads found the win-win solution. General mental abilities were not related to the detection of the win-win solution in either version. The paradigm provides a way to extend research on cooperation and conflict and can thus be useful in research and training.